Ectoparasite Analysis in Vaname Shrimp in Padang Pariaman, West Sumatra, Indonesia - Elfrida Elfrida; Amrona Rosida; Amelia Sriwahyuni Lubis; Abdullah Munzir; Ira Desmiati (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Ectoparasites pose a significant threat to the health and productivity of vaname shrimp (Litopenaeus vannamei) in aquaculture settings, particularly in tropical regions. This study aimed to assess the prevalence, intensity, and dominance of ectoparasites in vaname shrimp ponds in Padang Pariaman, West Sumatra, and to identify factors influencing their distribution. Sampling was conducted across five different pond stations, with each station subjected to regular water quality assessments, temperature monitoring, and parasitological examinations. Ectoparasites were identified and quantified using standard microscopic techniques to determine prevalence, intensity, and dominance. Results indicated that Station II had the highest prevalence (100%) and intensity (69) of ectoparasites, likely due to poor water quality, fluctuating temperatures, and inadequate pond management practices. In contrast, Stations I, III, IV, and V exhibited lower levels of ectoparasite infestation, with Station I having moderate prevalence (80%) and intensity (21) and the remaining stations showing relatively low infestation levels. The dominant ectoparasites identified were Epystylis sp, Zoothamnium sp, Vorticella sp, and Ichthyobodo sp, with varying levels of dominance across the stations, suggesting a correlation with environmental conditions and pond management practices. Effective management of water quality, stocking densities, and regular monitoring can help mitigate ectoparasite infestations in shrimp ponds. This research provides essential insights into sustainable shrimp aquaculture practices, emphasizing the importance of improved pond management strategies to enhance shrimp health and productivity while minimizing the impact of ectoparasites on aquaculture systems in tropical regions.